2020
DOI: 10.7759/cureus.9571
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Multivessel Severe Coronary Artery Disease in Patients With Non-ST Segment Elevation Myocardial Infarction Having Markedly Raised Cardiac Troponin T

Abstract: Introduction Non-ST segment elevation myocardial infarction (NSTEMI) is becoming more common than ST segment elevation myocardial infarction (STEMI) and data regarding presence of underlying multivessel coronary artery disease (MVCAD) in these patients is consistent in locoregional population that leads to lethal delays in proper management. Therefore, in the current study, we aimed to evaluate the frequency of MVCAD in NSTEMI with markedly raised troponin T levels. This will help to identify patients that sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, Pakistan is a resource limited country with lack of well developed screening programs due to which patients present late, leading to high rate of complications like left ventricular thrombosis [12]. Moreover, frequency of multi-vessel disease even in the absence of ST segment elevation on electrocardiogram is high [13]. Our results showed that diabetes and smoking were signi cantly associated with MI.…”
Section: Discussionmentioning
confidence: 63%
“…However, Pakistan is a resource limited country with lack of well developed screening programs due to which patients present late, leading to high rate of complications like left ventricular thrombosis [12]. Moreover, frequency of multi-vessel disease even in the absence of ST segment elevation on electrocardiogram is high [13]. Our results showed that diabetes and smoking were signi cantly associated with MI.…”
Section: Discussionmentioning
confidence: 63%
“…However, Pakistan is a resource-limited country with a lack of well-developed screening programs due to which patients present late, leading to a high rate of complications, like left ventricular thrombosis [ 13 ]. Moreover, the frequency of multi-vessel disease, even in the absence of ST-segment elevation on the electrocardiogram, is high [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advances in the study of heart diseases have led to the discovery of a broad range of novel biomarkers associated with cardiovascular risks, including cTnI and cTnT, B-type natriuretic peptide (BNP) and its prohormone NT-proBNP, C-reactive protein (CRP), myeloperoxidase (MPO), lipoprotein-associated phospholipase A2, miRNA, matrix metalloproteinases, and cystatin C [69,70]. Although these biomarkers have a prognostic value independent of the previous traditional risk factors, they have some limitations as early markers for ACS, including unstable angina, non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI) [69,71].…”
Section: іма As a Marker For Diseasesmentioning
confidence: 99%